Exploring the Cosmos of Data: Unleashing the Potential of IPFS (Interplanetary File System) for Decentralized Storage - Akanksha Singh; Harsh Vardhan Gupta; Vaishnavi Gupta (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Decentralized storage has emerged as a transformative solution for data storage by leveraging the power of blockchain technology. This paper explores the concept of decentralized storage and its practical implementation through Pinata on the Ethereum blockchain. The process involves connecting to the decentralized network through a wallet, utilizing a smart contract, and securely storing data on the Ethereum platform with the assistance of the Metamask wallet. Decentralized storage provides an alternative to traditional centralized storage solutions by distributing data across a network of nodes instead of relying on a single centralized entity. This approach offers benefits such as enhanced security, immutability, and fault tolerance. To realize decentralized storage, Pinata is a widely used platform that offers decentralized file storage and retrieval services on various blockchain networks. Pinata operates by connecting users to decentralized networks, such as IPFS (InterPlanetary File System), and facilitating the storage of data as files on these networks. Users can securely store their data by creating an account, connecting their wallet (e.g., Metamask), and interacting with Pinata's API. The use of a smart contract ensures transparency and trust in the storage process. In the context of decentralized storage on the Ethereum blockchain, the Metamask wallet plays a crucial role.